KONTRIBUSI PEMAHAMAN KOSAKATA ESP TERHADAP HASIL BELAJAR MAHASISWA TEKNIK SIPIL DI UNIVERSITAS EKASAKTI PADANG - SURI, ELDA MARTHA (journal of residu, 2019)
This research aims to reveal how much the contribution of ESP vocabulary understanding to the learning outcomes of students majoring in Civil Engineering at UNES Padang. This study is a correlational study. The number of samples of the study was 39 students, divided into 3 levels of entrance year, which started from the 2016 academic year until the 2018 academic year, with the selection of research samples using proportional random sampling techniques. The research data used are primary data and secondary data. Primary data is data obtained directly from research respondents through tests on vocabulary understanding of ESP Civil Engineering UNES Padang. Meanwhile, secondary data is data obtained from the learning outcomes of UNES Padang Civil Engineering students. And data collection techniques in this study are documentation. Documentation is the collection of data obtained from various written sources or documents. The data obtained are vocabulary data (ESP vocabulary) and learning outcomes of UNES civil engineering students in the 2018/2019 school year at Ekasakti University, Padang, so the data analysis technique used in this study is the normality test only. The results of this study indicate that contributing between ESP vocabulary understanding of civil engineering student learning outcomes at UNES Padang. The results show that understanding ESP 39 or 100% valid vocabulary.